PENDIDIKAN KARAKTER PADA SISWA BERBASIS TAZKIYATUN NAFS DI SD NEGERI 1 KEMBARAN KULON KECAMATAN PURBALINGGA KABUPATEN PURBALINGGA - Akhmad, Fandi (El-Hamra, 2019)
Elementary school children are the next generation who will determine the fate of a nation in the future. The character of elementary school children formed today will determine the character of a nation in the future. Character education in the elementary school environment then plays a very important role. This is because it can improve the quality of implementation and the results of education in schools that lead to the achievement of the formation of character and commendable morals in students. The character of elementary school students can be built in several ways. The results of the study stated that in SD Negeri 1 Kembaran Kulon, Purbalingga Subdistrict, Purbalingga Regency, character education based on Tazkiyatun Nafs was developed in the Islamic religious education curriculum and incorporating the values ??of tazkiyatun nafs in the student, daily, weekly, monthly basis education program. And the involvement of educators in the student habituation program. Character education is carried out in an integrated manner in each subject, the development of school culture, extracurricular activities and daily activities of students at home Key Words: Character Education, Tazkiyatun Nafs